2008
DOI: 10.1177/0363546507312645
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Failure and Cartilage Damage during Knee Joint Compression

Abstract: Cartilage injury arising at the time of ACL injury may lead to an accelerated risk of joint degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 36 publications
(42 reference statements)
2
42
0
Order By: Relevance
“…Theories have proposed various contributors to or risk factors for injury: intrinsic [1][2][3][4] and extrinsic 1,[4][5][6] entities; the antagonist-agonist relationships 7,8 ; quadriceps contraction 4 ; and, more recently, axial compressive forces on the lateral aspect of the joint [9][10][11][12] . Initial reports on mechanisms of anterior cruciate ligament injury were based on interviews with the athletes or descriptive analyses of videotapes 1,5,13 .…”
mentioning
confidence: 99%
“…Theories have proposed various contributors to or risk factors for injury: intrinsic [1][2][3][4] and extrinsic 1,[4][5][6] entities; the antagonist-agonist relationships 7,8 ; quadriceps contraction 4 ; and, more recently, axial compressive forces on the lateral aspect of the joint [9][10][11][12] . Initial reports on mechanisms of anterior cruciate ligament injury were based on interviews with the athletes or descriptive analyses of videotapes 1,5,13 .…”
mentioning
confidence: 99%
“…(2) There is emerging evidence from recent scientific findings that the mechanism of ligament injury-derived OA begins with ligament injury and the subsequent changes in ligament mechanics and biochemistry that renders the joint unstable [35,52,53].…”
Section: Ligament Laxity -Pathway To Chronic Joint Pain and Osteoarthmentioning
confidence: 99%
“…The rate of loading was based on a single 10-Hz haversine curve, simulating the impact experienced during landing. 15 Dental cement (Base-liquid and powder, Dentsply, Tianjin, China) was used to secure the explant in the potting cup. Each explant was immersed in medium and a 10-N pre-loading was introduced by spatially adjusting the actuator via MTS to ensure contact between the compression plate and the explant.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…Thambyah et al 14 found that menisci-covered cartilage exhibited considerably larger modulus by $70%, and was thinner than exposed cartilage by $40%; subchondral bone quantity and calcified layer thickness were also significantly lesser. Yeow et al 15 further underscored that exposed regions do not generally sustain more damage than neighboring menisci-covered regions during a simulated landing impact of the knee joint; this observation suggested that the exposed cartilage region is more primed for load-bearing than its meniscicovered counterpart. However, it is not fully understood whether these regions also possess different levels of susceptibility to degeneration, which may be more relevant for understanding post-traumatic OA.…”
mentioning
confidence: 99%
See 1 more Smart Citation